Effect of Bar-Code Technology on the Safety of Medication Administration - Poon, Eric G; Keohane, Carol A; Yoon, Catherine S; Ditmore, Matthew; Bane, Anne; Levtzion-Korach, Osnat; Moniz, Thomas; Rothschild, Jeffrey M; Kachalia, Allen B; Hayes, Judy; Churchill, William W; Lipsitz, Stuart; et al. (The New England journal of medicine, 2010)
This study from a large academic hospital looked at medication errors before and after the implementation of technology for bar-code electronic medication-administration records. After implementation of the bar-code system, errors in transcription of medication orders were eliminated and errors in medication administration and potential drug-related adverse events were reduced. After implementation of a bar-code system, errors in transcription of medication orders were eliminated and errors in medication administration and potential drug-related adverse events were reduced. Medication errors in hospitals are common 1 , 2 and often lead to patient harm. One study identified 6.5 adverse events related to medication use per 100 inpatient admissions; more than one fourth of these events were due to errors and were therefore preventable. 2 Among serious medication errors, about one third occur at the ordering stage of the medication process, another third occur during medication administration, and the remaining third occur in about equal numbers during the transcription and dispensing stages. 3 Health care information technology has been touted as a promising strategy for preventing medication errors. 4 – 6 For example, computerized physician-order entry . . .